Dampak Dana Spontan Terhadap Persekutuan Ibadah di Jemaat GMIM Eben Haezer Pahaleten Wilayah Kakas Satu - Maindoka, Brela Agnesia; Sarimbangun, Ramli (Educatio Christi, 2023)
This article aims to conduct an in-depth analysis of the impact of spontaneous funds on the communion of worship at the GMIM Eben Haezer Pahaleten Congregation in the Kakas Satu Region. The problem that arises is related to this spontaneous fund, where the collection is no longer like the beginning of its formation so that the congregation feels uneasy about this behavior. The research method used to solve this problem is a qualitative research method with the stages of collecting scientifically tested literature exploration such as books and journals, without ignoring field data. If the implementation of this spontaneous fund is carried out in a good way, it will have a good impact, on the other hand, if it is taken in an inappropriate way, it will have a bad impact. This paper ends with a conclusion that contains the achievement of research objectives.